Does magnesium dysbalance participate in the development of insulin resistance in early stages of renal disease? - Sebeková, K; Stefíková, K; Polakovicová, D; Spustová, V; Dzúrik, R (Physiological research, 2002)
We investigated the potential role of magnesium (Mg) dysbalance in the pathogenesis of insulin resistance (IR) in patients with mildly-to-moderately decreased renal function (creatinine: 142.8+/-11.0 mmol/l). The data were compared to those of 8 age- and sex-matched healthy controls (CTRL). The standard oral glucose tolerance test (oGTT) was performed in 61 patients. Twenty-two patients were classified as IR according to their values on fasting and after-load immunoreactive insulin concentrations. Serum and total erythrocyte Mg (tErMg) (atomic absorption spectro-photometry) and free erythrocyte Mg (fErMg) concentrations ((31) P NMR spectroscopy) were determined prior to and two hours after the glucose load. Ten out of 39 insulin-sensitive (IS) patients, but only one out of 22 insulin-resistant (IR) patients, had a low basal fErMg concentration (<162.2 micromol/l, chi2, p<0.01). IR patients had higher serum Mg, total erythrocyte Mg and bound erythrocyte Mg (bErMg) concentrations (both before and after glucose load) when compared with the IS group. Both groups responded to the glucose load with a significant decrease in serum Mg concentration (within the normal range), while the IR group also exhibited a decline in tErMg and bErMg. The mean sum of insulin needed to metabolize the same glucose load correlated positively with tErMg (r=0.545, p<0.01) and bErMg (r=0.560, p<0.01) in the IR patients. It is concluded that, at an early stage of renal dysfunction, IR is not associated with the decline in free erythrocyte Mg concentration, but the magnesium handling in red blood cells is altered.
Keywords: nemoci ledvin; Magnesium; dospělí; hořčík; glukózový toleranční test; Female; Water-Electrolyte Balance; Adult; ženské pohlaví; Nephrosclerosis; erytrocyty; lidé; nefroskleróza; Glucose Tolerance Test; Nephritis, Interstitial; Kidney Diseases; Middle Aged; vodní a elektrolytová rovnováha; Erythrocytes; Male; Insulin Resistance; index tělesné hmotnosti; inzulinová rezistence; lidé středního věku; mužské pohlaví; Body Mass Index; Glomerulonephritis; glomerulonefritida; intersticiální nefritida; Humans